Cerebral hemodynamics in arteriovenous malformations: evaluation by single-photon emission CT. - Takeuchi, S; Kikuchi, H; Karasawa, J; Naruo, Y; Hashimoto, K; Nishimura, T; Kozuka, T; Hayashi, M (American Journal of Neuroradiology, 1987)
Cerebral hemodynamics in six patients with supratentorial arteriovenous malformations (AVMs) were studied by using single-photon emission CT with three types of radioactive isotopes: N-isopropyl-p-[123I] iodoamphetamine, 81mKr, and 99mTc-RBC in order to determine the local cerebral blood flow and blood volume associated with these malformations. The AVMs were shown to have high flow while other areas of the brain, including the contralateral hemisphere, had variable areas of diminished perfusion. There was increased blood volume in the regions of AVMs, and poor but evenly distributed blood volume in the other regions. CO2 reactivity during hypocapnia was preserved throughout the brain except for the region of the AVMs. In large AVMs, the ischemic state surrounding the nidus was considered to be caused mainly by the cerebral steal phenomenon.